Nilai Ekonomi Pekarangan: Program Pekarangan Pangan Lestari Kabupaten Agam - Lusiani, Gustina; Maryanti (Jurnal Informatika Ekonomi Bisnis, 2024)
This study aims to analyze the economic value of the Sustainable Food Garden Program (P2L) in Agam Regency. A quantitative method was applied with a sample of 50 respondents selected using proportionate random sampling. Data was collected through questionnaires and documentation and analyzed using farm income tests, B/C and R/C ratios, as well as paired t-tests. Results indicate that the average annual net income from home gardens reaches IDR 1,551,432, with a B/C ratio of 3.85 and an R/C ratio of 4.73, suggesting the economic feasibility of this activity. The P2L program contributes 5.04% to total household income, helping to reduce household expenses for vegetables and herbal medicines. Based on paired t-test results, household income was found to increase by IDR 129,286 per month after program implementation, significant at a 95% confidence level. The P2L program has proven effective in improving family welfare through optimal use of home garden space.